Microfluidic plasma extraction from blood using wash-free pneumatic system - Lin, Yun Jia (Nanyang Technological University, 2023)
Point-of-care (POC) plasma extraction is significant in the healthcare field as it can overcome challenges associated with manual centrifuges, including sample transportation time causing cell degradation and activation, especially in platelets, which may affect the accuracy and reliability of the result. Manual centrifuges are also not suitable for POC plasma extraction due to inconsistent process flow and the need for skilled operators. POC plasma extraction involves the immediate separation of plasma from whole blood at the point of care, allowing for more consistent and accurate blood test results. This process ensures that the plasma is extracted quickly and efficiently, reducing the risk of hemolysis, which can occur when blood cells break down and release their contents into the plasma. This can interfere the accuracy of blood test results, particularly for tests that measure the concentration of enzymes or proteins that are released from damaged blood cells.